A Model for Culinary Business Development Using Digitalization and Halal Food to Enhance Local Product Competitiveness in Coastal Villages - Siswati, Endang; Rapitasari, Diana; Kharismawati, Ika (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
This study aims to determine and analyze the potential and challenges of culinary businesses, the implementation of digitalization and halal certification, and the development of an effective and sustainable model for the "Resto Apung" culinary business to support food economic independence in coastal villages. The research was conducted at "Resto Apung" using a qualitative descriptive method with data collection techniques such as interviews, observations, and focus group discussions. The findings show that the "Resto Apung" business holds significant potential as a culinary destination with a strong attraction due to its unique location and menu offerings based on local marine products. However, several challenges hinder its development, including low digital literacy among business managers, lack of structured and professional management systems, and the absence of halal certification which is crucial in targeting broader Muslim consumer segments. Currently, digitalization has only been applied in the marketing aspect, primarily through social media, while other aspects such as financial management, customer service, and operational processes are still managed conventionally. Nevertheless, the managers have shown awareness and initiatives to improve, especially in recognizing halal certification as a strategic competitive advantage. The proposed development model integrates digitalization into all aspects of business management, enhances human resource capacity through technical and managerial training, and includes efforts to obtain halal certification. This holistic approach is expected to increase the competitiveness of the culinary business, optimize local potential, and ultimately contribute to the achievement of food economic independence in coastal areas.